Pendampingan Belajar Melalui Kegiatan Bimbingan Belajar pada Materi Penjumlahan dan Pengurangan Pecahan Bagi Siswa Sekolah Dasar - Nurdiana Siregar; Ahmad Fajar Awalushihab; Umira Khairinia Absa; Safriza Ariska Sitorus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Students who do not understand the material for adding and subtracting fractions will have difficulty learning further math material, due to the hierarchical and interrelated nature of mathematics itself. If material that students have not understood is left or ignored, mathematics will become a mystery forever to him. Therefore it is necessary to immediately assist students who have difficulty in learning mathematics material. The solution offered is to apply learning assistance in the form of tutoring activities where the material is explained again, students are guided and trained to solve questions, which is done continuously and repeatedly until the student is able to independently answer the questions correctly. The learning assistance activities that have been carried out have had an impact on students in grades V and VI who have difficulty in adding and subtracting fractions, seen from an average of 17 to 96. Student learning outcomes have increased after the learning assistance activities, out of 16 students there were 14 students who scored 90 and 100, and two others scored 80.